Identificacion Espacial De Areas Con Amenaza De Incendio Forestal En Elmunicipio De Cota Cundinamarca, Empleando Sistemas De Informacion Geografica A Escala 1:25.000 (2023)
This technical project contains the zoning of the threat of forest fires of vegetation cover with a scale of 1:25,000 in the municipality of Cota, Cundinamarca, which covers an area of 52 km2, where a large amount of territory belongs to the environmental protection area. the Serró del Majuy where in past years there were forest fires.